Philosophy of Alexander Bykhovskii’s Creative Work: Art and Poetry (1888–1978) - Mentiukova (Ivanova), Olga K. (Actual Problems of Theory and History of Art, 2015)
Alexander Bykhovskii was a Russian artist who worked in 1910–1950s and the author of works of different types and genres of plastic arts, including graphic works, poster, sculpture, decorative and applied arts. Style of Bykhovskii’s works has a strong link with expressionism, constructivism and realistic art at the same time. Besides painting, Bykhovskii wrote a lot critical essays and articles about theory and history of art. We examined the artist’s manuscripts in order to find out the main aspects of his ideology and to search connection between his philosophy and his art. As a result we can conclude that the main aspects of philosophy of Bykhovskii’s creativity are: cosmism, expressivity and dynamism, optimistic and dramatic senses, monumentalism. Also we examined Bykhovskii’s attitude toward classical art and discovered the antique reminiscences in some of his works. Though Bykhovskii’s philosophy of creativity was somehow typical for his epoch, his creative development was different from both the soviet official and vanguard artists, and the figure of Bykhovskii is quite unique in the history of Russian art.
Keywords: philosophy of creativity; aesthetic conception; aesthetic theory; theory of art; political poster; expressionism; constructivism; vanguard; Russian vanguard; cosmism; decorative and applied arts